Fibrinolysis - Tuddenham, Edward (Henry Stewart Talks, 2007)
Biochemistry and physiology of fibrinolysis, The balance of fibrinolysis in blood, activators and inhibitors, Assays of fibrinolysis, clot lysis, model thrombi under flow, in situ zymography and euglobulin lysis, Genetic deficiency syndromes
Reviewed at 2015/09/30